The Effect of Land Tenure on Agricultural Household Income and Welfare in Different Agroecosytems - Mutiara Budi Amalia; Harianto Harianto; Sumaryanto Sumaryanto (Jurnal Agribisnis Indonesia, 2023)
Narrowing land tenure is happening in Indonesia agricultural household. This affect on decreasing agricultural household income. Attempts to increase income in the non-agricultural sector have resulted in a variety of income structures. The relationship between land tenure and household income does not always show the same direction, this is due to different agro-ecosystem conditions. This study aims to analyze: (1) the effect of land tenure and agro-ecosystem conditions on the non-agricultural income structure, (2) the effect of land tenure and non-agricultural income structure on the welfare of agricultural households. The data used is the National Farmer Panel sourced from the Indonesian Center of Agriculture Socio Economics Policy Studies (ICASEPS), Ministry of Agriculture. The analytical method used is Generalized Linear Model whics is processed using R Software. The results show that there is a negative relationship between land area and non-agricultural income structure. Meanwhile, education and agro-ecosystem conditions are positively related to non-agricultural income structure. The percentage of non-agricultural income, sequentially from the highest, is the agro-ecosystem of paddy fieds, dry land based crops and vegetables, plantation-based dry land. A positive relationship is also shown between the variables of land area, education, non-agricultural income structures and the welfare of agricultural households which were proxied using per capita expenditure. Meanwhile, an increase in household members will reduce the welfare of agricultural households.